The Relantionship Characteristic and Relaps in Pulmonary Tuberculosis Patients at RSI PKU Muhammadiyah Pekajangan Pekalongan - Ratnawati, R; Arifin, Mokhamad (Prosiding University Research Colloquium, 2022)
Pulmonary tuberculosis is oner the tip 10 causes of death in the world. Indonesia is the country with the most pulmonary tuberculosis sufferers in 2020. Factors causing pulmonary tuberculosis reccurent include : age, gender, education, occupation and smoking. The study aimed to examine the relationship between the characteristics and the incidence of relaps in pulmonary tuberculosis patient at RSI PKU Muhammadiyah Pekajangan Pekalongan. This study used a descriptive design with a retrospective approach. Data collectin using medical records. The are 391 pulmonary tuberculosis patients involved in study. The results shoe that most of the pulmonary tuberculosis patiens aged 56-65 years (23,5%), male gender (53,5%), low education level (67%), working (60,1%), smoking (52,4%) and no reccurence (95,4%). The result the Spearman correlation test show that there was asignificant relationship between age (p = 0,001), gender (p = 0,002), education (p = 0,018) and smoking (p = 0,027) wit the incidence of relaps in pulmonary tuberculosis patients. There was no significant relationship between work (p = 0,562) with incidence of relapse in pulmonary tuberculosis patients at RSI PKU Muhammadiyah Pekajangan Pekalongan. Risk factor related to patient characterstics need to be considered in an effort to prevebt recurrent of pulmonary tuberculosis at RSI PKU Muhammadiyah Pekajangan Pekalongan.